The impact of fees on customer purchasing behavior and beliefs in winery tasting rooms: A scoping review - John Spence (Wine Economics and Policy, 2023)
Purpose: This scoping review presents a summary of studies that examined the impact or influence of tasting fees in wineries on the purchasing behaviour, beliefs, obligation to buy wine, and willingness to pay for such fees. Methods: A search was conducted in August 2021 and updated in March 2022 of databases (i.e., Academic Search Complete, Scopus) and hand searching using terms such as wine, tasting fees, and charges. Documents were included if they were databased studies, published in English, and related to the research question. They were then coded for characteristics of the document, design, sample, winery, purchasing behaviour and beliefs, and findings. The coding and analysis were conducted between August 2021 and March 2022. Findings: Of 195 possible documents, 16 remained after a title and abstract scan, and 12 were included after a full-article scan. The reviewed studies were conducted primarily in Australasia (60%) and North America (28%) and a majority of findings were derived from surveys or interviews. A majority of the findings suggested that customers and industry professionals did not support the adoption of tasting fees at the cellar door (64%). Though, mixed impact was noted for purchasing behaviour (i.e., volume, money spent), slightly stronger negative associations were seen for intention to visit the winery or purchase wine in the future, willingness to pay for fees, and obligation to buy wine. Originality: This is the first systematic review to examine the impact or influence of tasting fees on purchasing behaviour and beliefs in wineries.